2005
DOI: 10.1261/rna.2163106
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant viral RdRps can initiate RNA synthesis from circular templates

Abstract: The crystal structure of the recombinant hepatitis C virus (HCV) RNA-dependent RNA polymerase (RdRp) revealed extensive interactions between the fingers and the thumb subdomains, resulting in a closed conformation with an established template channel that should specifically accept single-stranded templates. We made circularized RNA templates and found that they were efficiently used by the HCV RdRp to synthesize product RNAs that are significantly longer than the template, suggesting that RdRp could exist in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 67 publications
2
25
0
Order By: Relevance
“…We therefore rule out that the 18 base pair DNA: RNA duplex segment contributes to NS5B binding. These observations are consistent with the reported narrow binding tunnel associated with the closed conformation of NS5B, which is unable to accommodate a double stranded segment (7,38,39).…”
Section: Resultssupporting
confidence: 91%
“…We therefore rule out that the 18 base pair DNA: RNA duplex segment contributes to NS5B binding. These observations are consistent with the reported narrow binding tunnel associated with the closed conformation of NS5B, which is unable to accommodate a double stranded segment (7,38,39).…”
Section: Resultssupporting
confidence: 91%
“…The replicases are usually difficult to study biochemically, but the catalytic RdRp subunits of several viruses can be purified for functional and structural analyses (53). These recombinant proteins can reproduce some of the activities of the replicases, including the ability to initiate RNA synthesis by a de novo mechanism (22,(47)(48)(49). Furthermore, recombinant RdRps can affect the activities of other replicase subunits in vitro, suggesting that the recombinant RdRp is useful for an in-depth understanding of RNA synthesis by HCV (45,60).…”
mentioning
confidence: 99%
“…Bovine viral diarrhea virus (BVDV) RdRp was also shown to exist in a partially open conformation (11). Ranjith-Kumar and Kao (49) demonstrated that the HCV RdRp could initiate RNA synthesis from a circular RNA template, and thus, the threading of a singlestranded RNA into the template channel is not required for de novo-initiated RNA synthesis. Altogether, these results raise the possibility that the HCV RdRp can undergo rearrangements from the closed conformation seen in the crystal structure prior to de novo initiation.…”
mentioning
confidence: 99%
“…RdRp assay mixtures contained 1 pmol of linear template RNA or 30 pmol of circular (C) template RNA and 0.04 M of NS5B protein (2,23). The assays were carried out in 20-l reaction mixtures containing 20 mM sodium glutamate (pH 8.2), 0.5 mM DTT, 4 mM MgCl 2 , 12, 0.5% (vol/vol) Triton X-100, 200 M ATP and UTP, and 250 nM [␣-32 P]CTP (MP Biomedicals).…”
mentioning
confidence: 99%